2021
DOI: 10.1108/ics-01-2020-0003
|View full text |Cite
|
Sign up to set email alerts
|

Forming digital identities in social networks: the role of privacy concerns and self-esteem

Abstract: Purpose This paper aims to identify the data elements that social network sites (SNS) users consider important for shaping their digital identity and explore how users’ privacy concerns, self-esteem and the chosen SNS shape this process. Design/methodology/approach This study conducted an online survey with the participation of 759 individuals, to examine the influence of privacy concerns, self-esteem and the chosen SNS platform, on the shaping of the digital identity, through a classification of identity el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
(106 reference statements)
0
10
0
2
Order By: Relevance
“…However, models have emerged that are designed to take these factors into account. Aghasian et al [13], for example, developed a system that factors in the fact that users may engage with different social networks in different ways, while Papaioannou et al [29] found that users faced with "social threats" behaved differently from users faced with "organisational threats". All these attempts to measure privacy concerns have demonstrated that it is a complex parameter, one of several which affect behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, models have emerged that are designed to take these factors into account. Aghasian et al [13], for example, developed a system that factors in the fact that users may engage with different social networks in different ways, while Papaioannou et al [29] found that users faced with "social threats" behaved differently from users faced with "organisational threats". All these attempts to measure privacy concerns have demonstrated that it is a complex parameter, one of several which affect behaviour.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aghasian et al [ 39 ] offer a scoring system that derives a “privacy disclosure score” for users, taking into account that they may use several social networks in different ways. Papaioannou et al [ 40 ] identify a distinction between “social threats” and “organisational threats”, where only concern about the former has an impact on disclosure of personal information; they find also that a user’s behaviour differs between different social media platforms, and that there is a connection between self-esteem and the amount of personal information revealed. Concern about privacy thus emerges as a rather variable element in a mesh of factors affecting behaviour.…”
Section: Background: Knowledge Sharing Information and Privacymentioning
confidence: 99%
“…Job satisfaction is closely related to the attitudes and behavior of employees to do their responsibility in the company, especially concerning the employee's own self-worth beliefs, including self-esteem (Papaioannou et al, 2021). Self-Esteem is an employee's perception of seeing and assessing the results achieved by analyzing how far the behavior meets their ideal (Bellou et al, 2018).…”
Section: H3: Self-efficacy Has a Positive Effect On Job Satisfactionmentioning
confidence: 99%